Role of gerontologist in activities in Open University Program for Third Age - Lima-Silva, Thais Bento (2013)
This study aimed to present the possibilities of action of BA in Gerontology - gerontologist, in the activities of continuing education through the Educational Gerontology. We conducted a non systematic literature review. This review indicated that the scene of action of the gerontologist in Open Universities of the Third Age involves since the creation, oversight, planning and conducting programs to promote health, to review the activities, in order to ensure that they prepare people for their own aging and retirement, with appropriate methodology to economic and cultural context of the target audience, encouraging empowerment and social participation. The acting in UnATI requests a look at the Educational Gerontology, which is helping to build the old age, giving the elderly the opportunity to change the course of your life and redirect your actions with freedom of choice.